Duodenal obstruction due to aneurysm abdominal aorta: First national communication and literature review - Kamaid Toth, Emil; Puñal, Alicia; Castelli, Fernando; Teixeira, Marcelo; Maglione, Oscar (Cirugía del Uruguay, 2006)
A 74-year-old male patient had vascular compression of duodenum caused by an aneurysm of abdominal aorta. Transit studied by barium, digestive endoscopy and CAT scan showed the extrinsic compression of the third portion of duodenum between the aneurysm and the upper mesenteric artery. Surgery confirmed diagnosis, the aorta was replaced by a prosthesis and the four portion was put back in place by sectioning the Treitz muscle. This is the first national report of a situation which is considered in literature as a very rare cause of superior mesenteric artery syndrome